Heterogeneous Social Preferences - Mathias Erlei (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2003)
Recent research has shown the usefulness of social preferences for explaining behavior in laboratory experiments. This paper demonstrates that models of social preferences are particularly powerful in explaining behavior if they are embedded in a setting of heteroge-neous actors with heterogeneous (social) preferences. For this purpose a simple model is in-troduced that combines the basic ideas of inequity aversion, social welfare preferences, recip-rocity and heterogeneity. This model is applied to 43 games and it can be shown that its pre-dictive accuracy is clearly higher than that of the isolated approaches. Furthermore, it can explain most of the "anomalies" (the "contradictions") that are discussed in Goeree and Holt (2001).
Keywords: C72; C92; D63; 330